Practitioners’ Experience in Clay 3D Printing: Metaphorical viewing for gaining embodied understanding - Falin, Priska; Horsanali, Nur; Tvede Hansen, Flemming; Mäkelä, Maarit (FormAkademisk, 2021)
In the context of artistic research, making has been traditionally understood as a process between the maker and the material. However, the digitalization that influences all practices brings us new kinds of making processes in which the ‘digital tools’ have a profound impact on the practitioner’s experience – also in the context of art, craft and design. This study explores the maker’s experience from a practice-led approach to understanding the subjective experience with clay 3D printing. To open up the 3D printing process with clay using our embodied understanding, the full process is viewed metaphorically – borrowing from music. The preliminary findings show that metaphorical viewing and the use of a score enables a successful review of the nature of computer-based practices in a way that all aspects and potentials fall naturally into place.